Identifying different phenotypes in takotsubo cardiomyopathy by latent class analysis. (26th November 2020) - Li, Pengyang; Dai, Qiying; Cai, Peng; Teng, Catherine; Pan, Su; Dixon, Richard A.F.; Liu, Qi
Abstract: Aims: This study sought to determine whether clinical clusters exist in takotsubo cardiomyopathy. Takotsubo cardiomyopathy (TCM) is a heterogeneous disorder with a complex, poorly understood pathogenesis. To better understand the heterogeneity of TCM, we identified different clinical phenotypes in a large sample of TCM patients by using latent class analysis (LCA). Methods and results: Using the National Inpatient Sample (NIS) database, we identified 3139 patients admitted to hospitals in 2016–2017 with a primary diagnosis of TCM. We performed LCA based on several patient demographics and comorbidities: age, sex, hypertension, hyperlipidaemia, diabetes mellitus, obesity, current smoking, asthma, chronic obstructive pulmonary disease (COPD), and anxiety and depressive disorders. We then repeated LCA separately with the NIS 2016 and 2017 data sets and performed a robust test to validate our results. We also compared in‐hospital outcomes among the different clusters identified by LCA. Four patient clusters were identified. C1 ( n = 1228, 39.4%) had the highest prevalence of hyperlipidaemia (93.4%), hypertension (61.6%), and diabetes (34.3%). In C2 ( n = 440, 14.0%), all patients had COPD, and many were smokers (45.8%). C3 ( n = 376, 11.8%) largely comprised patients with anxiety disorders (98.4%) and depressive disorders (80.1%). C4 ( n = 1097, 34.8%) comprised patients with isolated TCM and few comorbidities. Among all clusters, C1 had the lowest in‐hospital mortality (1.0%) and the shortest length of stay (3.2 ± 3.1 days), whereas C2 had the highest in‐hospital mortality (3.4%). Conclusions: Using LCA, we identified four clinical phenotypes of TCM. These may reflect different pathophysiological processes in TCM. Our findings may help identify treatment targets and select patients for future clinical trials.